2013
DOI: 10.1155/2013/137414
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance and the Role of Combination Chemotherapy in Improving Patient Outcomes

Abstract: Resistance to cancer chemotherapy is a common phenomenon especially in metastatic breast cancer (MBC), a setting in which patients typically have had exposure to multiple lines of prior therapy. The subsequent development of drug resistance can result in rapid disease progression during or shortly after completion of treatment. Moreover, cross-class multidrug resistance limits patient treatment choices, particularly in a setting where treatments options are few. One attempt to minimize the impact of drug resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 118 publications
1
125
0
2
Order By: Relevance
“…Combining chemotherapeutics with other agents is a novel treatment strategy for decreasing the lethal side effects. 39 In this study, we showed that a combination of DOX and balaglitazone at non-toxic concentrations caused a significant decrease in the IC 50 values of DOX in a concentrationdependent manner. Therefore, simultaneous treatment with DOX and balaglitazone reduced the DOX therapeutic dose and, more importantly, may relieve DOX-induced side effects without any changes in its efficacy.…”
Section: Discussionmentioning
confidence: 63%
“…Combining chemotherapeutics with other agents is a novel treatment strategy for decreasing the lethal side effects. 39 In this study, we showed that a combination of DOX and balaglitazone at non-toxic concentrations caused a significant decrease in the IC 50 values of DOX in a concentrationdependent manner. Therefore, simultaneous treatment with DOX and balaglitazone reduced the DOX therapeutic dose and, more importantly, may relieve DOX-induced side effects without any changes in its efficacy.…”
Section: Discussionmentioning
confidence: 63%
“…[10][11][12][13][14] These unique molecular features of TNBCs have precluded the development of FDA-approved targeted therapies against this BC subtype. [15][16][17][18][19][20][21] Moreover, the acquisition of chemoresistance is the main cause of disease recurrence and eventual death of BC patients, [22][23][24][25] particularly those harboring TNBC tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In this context the altered pH gradient across the cell membrane in cancer cells -extracellular acidification and alkalization intracellular -supports several of the above mentioned drug resistance mechanisms resulting for example in enhanced drug efflux (by drug enrichment in acidic vesicles, vesicular transport to the cell membrane and drug discharge in the extra cellular space [3,4] , diminished drug influx (impaired uptake of weakly basic chemotherapeutic drugs) or cell cycles arrest (restricted mTOR complex 1 activation with inhibition of protein synthesis and G0 and G1 cell cycle arrest) [6] .…”
Section: Mechanisms Of Drug Resistance In Cancer Cells and The Role Omentioning
confidence: 70%
“…The resistance of cancer cells towards several different drugs is called multidrug resistance (MDR) [2] . However, both, innate and/or adaptive resistance, critically limit treatment success and remain a key challenge for clinicians [3] .…”
Section: Introductionmentioning
confidence: 99%